2012
DOI: 10.1016/j.neurobiolaging.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and genetics of frontotemporal dementia: a door-to-door survey in Southern Italy

Abstract: The objectives of this study were to estimate frontotemporal dementia (FTD) prevalence, identify FTD-related mutations, and correlate FTD phenotype with mutations in a southern Italian population. The study population consisted of subjects ≥ 50 years of age residing in the Community of Biv. on January 1, 2004, and a door-to-door 2-phase design was used. Genetic and biochemical analyses were done on samples collected from 32 patients. Prevalence rates were 0.6 for Alzheimer's disease, 0.4 for vascular dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 29 publications
5
44
0
4
Order By: Relevance
“…Some missense GRN mutations produce normal PGRN plasma levels (A324T, R433W, P34S, P451L and C521Y; Sleegers et al, 2009; Finch et al, 2009; Almeida et al, 2014; Wang et al, 2010), while other missense GRN mutations produce intermediate PGRN plasma levels, between values typical of normal and null GRN mutations (C139R, R432C, R564C, C126W and A266P; Finch et al, 2009; Sleegers et al, 2009; Bernardi et al, 2012). Only the clearly pathogenic A9D mutation produces plasma PGRN levels typical of null GRN mutations (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some missense GRN mutations produce normal PGRN plasma levels (A324T, R433W, P34S, P451L and C521Y; Sleegers et al, 2009; Finch et al, 2009; Almeida et al, 2014; Wang et al, 2010), while other missense GRN mutations produce intermediate PGRN plasma levels, between values typical of normal and null GRN mutations (C139R, R432C, R564C, C126W and A266P; Finch et al, 2009; Sleegers et al, 2009; Bernardi et al, 2012). Only the clearly pathogenic A9D mutation produces plasma PGRN levels typical of null GRN mutations (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Only in 2006 the discovery of PGRN gene allowed to identify the causative gene in the Biv pedigree 16 . After ten years, a door-to-door population study in the same village showed an unusual higher incidence of FTD compared to AD and a high prevalence of GRN mutations, confirming the genetic peculiarity of this geographical area 17 .…”
mentioning
confidence: 61%
“…Regarding the sex distribution of FTD, there is a disagreement, as to whether there is a male predominance [22][23][24][25][26][27]. FTD is further subclassified by symptoms and presentation into two main categories: behavioral variant (bvFTD) and the language variant primary progressive aphasia (PPA) which is further divided into semantic dementia (SD) and progressive nonfluent aphasia (PNFA).…”
Section: Clinical Description Of Ftd and Alsmentioning
confidence: 99%